2013
DOI: 10.1002/2013gl058018
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric signatures of acoustic waves generated by transient tropospheric forcing

Abstract: [1] Acoustic waves generated by tropospheric sources may attain significant amplitudes in the thermosphere and overlying ionosphere. Although they are weak precursors to gravity waves in the mesosphere below, acoustic waves may achieve temperature and vertical wind perturbations on the order of approximately tens of Kelvin and m/s throughout the E and F regions. Their perturbations to total electron content are predicted to be detectable by groundbased radar and GPS receivers; they also drive field-aligned cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 23 publications
9
55
0
Order By: Relevance
“…The order of the amplitude of the typical magnetic fluctuations, main magnetic field, and the latitudinal spatial scale estimated from the CHAMP observation are 1 nT, 10,000 nT, and 100 km, respectively. Then, the order of density at the CHAMP altitude is 0.01 μ Am −2 , which is consistent with that predicted by Zettergren and Snively (2013).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The order of the amplitude of the typical magnetic fluctuations, main magnetic field, and the latitudinal spatial scale estimated from the CHAMP observation are 1 nT, 10,000 nT, and 100 km, respectively. Then, the order of density at the CHAMP altitude is 0.01 μ Am −2 , which is consistent with that predicted by Zettergren and Snively (2013).…”
Section: Resultssupporting
confidence: 89%
“…With the possibility of a tropospheric origin shown by computer simulation (Zettergren and Snively 2013), the field-aligned currents are caused by the propagation of acoustic gravity waves generated by tropospheric sources through the E-layer dynamo. The period of the acoustic wave is around 3.5 min, i.e., near the vertical resonance period.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that this feature of the TEC perturbations is related to the local magnetic field geometry [Heki and Ping, 2005;Shinagawa et al, 2007]. Recent detailed simulations by Zettergren and Snively [2013] have confirmed that the geomagnetic field does induce significant anisotropy in TEC perturbations produced by a weather-related source of low-frequency acoustic waves which agree remarkably well with signatures reported by Nishioka et al [2013].…”
Section: Introductionsupporting
confidence: 66%
“…After great earthquakes, short-period magnetic and atmospheric pressure oscillations (e.g., Iyemori et al 2005Iyemori et al , 2013 or TEC variations (e.g., Otsuka et al 2006;Saito et al 2011) were observed. As to the theoretical study, TEC oscillations observed after the 2011 off the Pacific coast of Tohoku Earthquake and FACs in the ionosphere generated by acoustic mode waves were well reproduced with numerical simulations by Matsumura et al (2011) and by Zettergren and Snively (2013), respectively. Zettergren and Snively (2015) performed the computer simulations showing that TEC and ground-level magnetic field perturbations and dynamo FACs can be caused by natural hazard events including volcanic eruptions.…”
Section: Introductionsupporting
confidence: 65%